ANALISIS EVOLUSI EKOSISTEM PERANGKAT LUNAK OPEN SOURCE : TINJAUAN PUSTAKA SISTEMATIS - Angreni, Dwi Shinta; Prastyaningsih, Yunita (ScientiCO : Computer Science and Informatics Journal, 2019)
The development of an Open Source Software (OSS) can influence the development of other Open Source Systems. The relationship between OSS is often called an ecosystem, there are several aspects to the OSS ecosystem that can affect ecosystem evolution in the software. This study reports a systematic literature review on the influence of several aspects of the OSS ecosystem on the evolution of OSS. The Sistematic Literature Review method based on Kitchenham was used to analyze 1099 articles published in leading journals and conferences. The Results showed that Social aspects have a significant impact on ecosystem evolution, where communication between communities in an OSS ecosystem influences aspects of contributions and dependencies that encourage an ecosystem to develop and evolve.